أدب الرحلة في عصر الرقمنة: Travel Literature in the Digital Age (Contemporary Journal of Social Science Review, 2025)
The historical development of Arabic travel literature is deeply rooted in the traditional genre of travelogue, which dates back to the middle Ages. These travelogues were not only travel narratives but also vehicles for scientific, cultural, and religious exploration. In the nineteenth century, this genre underwent a major transformation as Arab writers began to engage with European modernity and technological advancements. Now we live in an era of technological revolution, witnessing new technologies in all areas of life every day. Digital technology is now the backbone of life in the digital age.            Cultural narratives have become more interactive and participatory. Social media platforms have enabled authors to interact directly with their audiences, creating a new dynamic between writers and readers. The advent of the internet has transformed travelogues from static texts into dynamic, multimedia narratives. For example, contemporary pilgrimages have evolved into "mobile literature," including live broadcasts and video blogs. These digital narratives provide vivid, interactive accounts of religious and cultural experiences. This article is a simple attempt to shed light on this genre of literature to meet the needs of the contemporary era.             This article will discuss: the concept of digital literature, technological platforms, Arabic digital travel literature, the reasons for the spread of digital literature, the types and characteristics of digital literature, the tools and mechanisms of digital literature, and audience engagement in Arabic digital travel literature. Discussing all of these points will help us gain insight into the transformative potential of this genre in the digital age. As digital technologies continue to evolve, Arabic travel literature is likely to remain a vibrant and evolving field, shaped by the creative and critical engagement of writers, audiences, and platforms.